Capturing Qualitative Data: Northwestern University Special Libraries' Acknowledgments Database. - Stigberg, Sara; Guittar, Michelle; Morse, Geoffrey (Portal: Libraries & the Academy, 2015)
Assessment and supporting data have become of increasing interest in librarianship. In this paper, we describe the development and implementation of the Northwestern University Library Acknowledgments Database tool, which gathers and documents qualitative data, as well as its component reporting function. This collaborative project and resulting products demonstrate how librarians and library staff, who are generally not experts in programming and software development, can successfully produce practical and functional tools to achieve their assessment goals.